Effect of Long Extended Working Hours on the Occupational Health and Safety of Oil and Gas Workers in the Sultanate of Oman - Suvarnaraju Palathoti; Abdullah Hamed Muhanna Al Aghbari; Victor O. Otitolaiye (Occupational Health and Safety Society of Nepal, 2023)
Introduction:  Oil and Gas workers are exposed to numerous hazards which impede their productivity; one such hazard these workers are exposed to is long or extended working hours. Hence, this paper examined the impacts of extended working hours on workers' occupational health and safety at a selected oil and gas company in Oman. Consequently, the workers' opinions on the impacts of extended working hours at the company were critically analyzed to draw potential inferences and proffer solutions to the problem in Oman. The study aimed to critically identify, assess, and highlight the occupational safety problems associated with extended working hours among workers at a selected oil and gas company in Oman. Methods: A total of 128 respondents were randomly selected from the 140 employees and company managers through administered questionnaires. Data collection was done between January 25 and February 30, 2022. The questionnaire consisted of five items statements based on the four-agreement or Likert scale of measurement. Results: A response rate of 91% was derived from the questionnaire administered for the study. Results from data analysis indicated that 73% of the respondents were male while 27% were female. Furthermore, the results indicated that extended working hours have substantial impacts on family life (s=54%), performance (s=68%), productivity, and health of the workers. Extended working hours potentially expose workers to various dangers which bring about numerous adverse effects (stress, fatigue, depression, and loss of concentration) on their occupational health and safety. Conclusion: It is recommended that oil and gas companies establish occupational health and safety guidelines to limit the work times and duration (i.e., time spent at work) through shorter shifts, longer breaks, or extended leaves. Long working hours should be prohibited except on special occasions or unavoidable circumstances to safeguard the health and well-being of staff, which could ultimately enhance the productivity and output of the company.